2022
DOI: 10.3390/bios12020117
|View full text |Cite
|
Sign up to set email alerts
|

Hammerstein–Wiener Multimodel Approach for Fast and Efficient Muscle Force Estimation from EMG Signals

Abstract: This paper develops a novel approach to characterise muscle force from electromyography (EMG) signals, which are the electric activities generated by muscles. Based on the nonlinear Hammerstein–Wiener model, the first part of this study outlines the estimation of different sub-models to mimic diverse force profiles. The second part fixes the appropriate sub-models of a multimodel library and computes the contribution of sub-models to estimate the desired force. Based on a pre-existing dataset, the obtained res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…We used sEMG to demonstrate the positive effects of yoga on balance, which was rare in previous studies. Previous studies showed that sEMG was able to accurately measure muscle activity through bioelectrical changes [50, 51, 52]. TA played an important role in the stabilization of OLS [53], and the stability of the sEMG signal amplitude during the process of maintaining balance meant the improvement of balance efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used sEMG to demonstrate the positive effects of yoga on balance, which was rare in previous studies. Previous studies showed that sEMG was able to accurately measure muscle activity through bioelectrical changes [50, 51, 52]. TA played an important role in the stabilization of OLS [53], and the stability of the sEMG signal amplitude during the process of maintaining balance meant the improvement of balance efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…We used sEMG to demonstrate the positive effects of yoga on balance, which was rare in previous studies. Previous studies showed that sEMG was able to accurately measure muscle activity through bioelectrical changes [50,51,52].…”
Section: Effects Of Practicing Yoga As a Long-term Warm-up On Balancementioning
confidence: 99%
“…On the other hand, their particular structure allows for the extension of certain results obtained within the framework of linear systems [34].…”
Section: Fractional Order Takagi-sugeno Model Approachmentioning
confidence: 99%
“…[7]. An input nonlinear autoregressive exogenous (IN-ARX) model has been applied in different disciplines, such as multi-input multi-output (MIMO) systems [8], muscle modeling [9], data filtering [10], wireless sensor network [11], control systems [12], and electromyography [13].…”
Section: Introductionmentioning
confidence: 99%